Analysis of desmin and vimentin phosphopeptides in cultured avian myogenic cells and their modulation by 8-bromo-adenosine 3',5'-cyclic monophosphate. - Gard, D L (1982)
The intermediate filament proteins desmin and vimentin are two of the major 32P phosphate acceptors in chicken myotubes differentiating in tissue culture. Analysis of the desmin and vimentin phosphopeptides by two-dimensional tryptic peptide mapping shows that both proteins are phosphorylated at multiple sites, giving rise to 5 phosphopeptides in desmin and as many as 11 in vimentin. Addition of the cAMP analogue 8-bromoadenosine 3',5'-cyclic monophosphate (8-BrcAMP) to the culture medium of mature (8-day-old) myotubes results in a 2- to 3-fold increase in PO4 incorporation into desmin and vimentin. Two-dimensional tryptic analysis of desmin and vimentin from 8-BrcAMP-treated myotubes shows increased 32PO4 incorporation into a subset of the phosphopeptides observed in control cells. Comparison of phosphopeptides from the two proteins shows the presence of at least three comigrating peptides. All three comigrating peptides exhibit cAMP-dependent increases in 32PO4 incorporation in vimentin, while only two of the three exhibit 8-BrcAMP-dependent responses in desmin. While these peptides are the only two that are sensitive to 8-BrcAMP in desmin, vimentin contains additional peptides that exhibit increased 32PO4 incorporation in response to 8-BrcAMP. This result suggests the existence of both common and distinct phosphorylation sites between desmin and vimentin that may be differentially regulated by cAMP. Thus, desmin and vimentin, even though structurally related, may be capable of responding differently to physiological stimuli.